2012
DOI: 10.2500/ar.2012.3.0020
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Comparison in Common Rhinologic Surgeries

Abstract: Various questionnaires are used in patients who undergo rhinologic surgeries but a unique comprehensive questionnaire is needed to evaluate quality of life (QOL) in rhinologic surgeries. The purpose of this study was to prepare a comprehensive questionnaire and compare QOL among four common rhinologic surgeries including functional endoscopic sinus surgery, septoplasty, septorhinoplasty, and septoplasty with turbinoplasty preoperatively and 6 months postoperatively. This was a prospective interventional before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 15 publications
(31 reference statements)
1
16
0
1
Order By: Relevance
“…According to their results, sinus patients had a significantly lower HRQoL measured using the generic SF‐36 instrument, compared to septum patients irrespective of age and sex . In another study, a comparison of the preoperative HRQoL amongst four rhinologic surgical groups also showed differences between these groups . By contrast, a recent Finnish study investigating septoplasty and FESS patients preoperatively reported results comparable to our study.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…According to their results, sinus patients had a significantly lower HRQoL measured using the generic SF‐36 instrument, compared to septum patients irrespective of age and sex . In another study, a comparison of the preoperative HRQoL amongst four rhinologic surgical groups also showed differences between these groups . By contrast, a recent Finnish study investigating septoplasty and FESS patients preoperatively reported results comparable to our study.…”
Section: Discussionsupporting
confidence: 68%
“…To our knowledge, no similar comparison and investigation of unselected rhinologic patients appears in the literature. Furthermore, the total number of patients in our study was higher than in most previously published HRQoL studies . In addition, the advantage of the 15D instrument used in this study is that it has also been used to study patients with several other health conditions from the same metropolitan area .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In their recent prospective observational study, Kahveci et al [11] reported that septoplasty without turbinate reduction yields a marked improvement in the NOSE scores of patients at six months after the operation and concluded that the NOSE scale is a very useful tool for evaluating the effectiveness of pure septoplasty. Similarly, Naraghi et al [15] found in their prospective interventional study that septoplasty has a profound effect on the general QoL of patients six months after the operation. They used a modified health-related QoL instrument and concluded that the correction of septal deviation not only alleviates the obstructive nasal symptoms but also improves general QoL.…”
Section: Discussionmentioning
confidence: 86%
“…This could also be used for nasal irrigation post surgery [126]. Naraghi et al found that the quality of life was improved significantly in patients after FESS [128]. FESS should be done with great care especially in those with AFS because in them bone dissolution is common and there is a potential risk of inadvertent penetration into orbit or cranium [129].…”
Section: Managementmentioning
confidence: 99%